The Effect Of Remote Working On Employee Performance With Job Satisfaction As Intervening Variable - Sya'bani, Fadhilah; Noermijati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this study is to identify the effects of remote working on employee performance and the influence of job satisfaction as an intervening variable in the relationship between remote working and employee performance in the context of fintech companies in Indonesian. Using purposive sampling technique, 125 people who live in Indonesia and work remotely for fintech companies were selected as the respondents of this quantitative explanatory research. The data was harvested from questionnaires and was examined using descriptive analysis and path analysis. The hypothesis testing was conducted using t-test. All of the statistical analysis was performed in IBM SPSS 29. This study finds that remote working significantly affects employee performance and that job satisfaction mediates the impact of remote working on employee performance.